The terracotta warriors : exploring the most intriguing puzzle in Chinese history - Burman, Edward (Pegasus Books, 2018)
Traces the discovery of the famed terracotta warriors against a backdrop of what is currently known about the Qin Dynasty, offering scholarly insights into the surprising theories about the creation of the Qin Emperor's remarkable third-century B.C.E. mausoleum.